Convective Precipitation Efficiency Observed in the Tropics. Issue 22 (27th November 2019) - Narsey, Sugata; Jakob, Christian; Singh, Martin S.; Bergemann, Martin; Louf, Valentin; Protat, Alain; Williams, Christopher
Abstract: Precipitation efficiency refers to the fraction of condensate in the atmosphere that reaches the surface as precipitation. A high‐quality data set of radar‐estimated precipitation rates and convective scale vertical velocity near Darwin, Australia, is used to construct the first estimate of precipitation efficiency at convective scales for a long record of observations in the tropics. It is found that precipitation efficiency increases with precipitation rate and midtropospheric humidity and decreases with increasing convective available potential energy and surface temperature. Precipitation efficiency is largest under moist monsoonal conditions and smallest during monsoon break periods, which are characterized by a drier free troposphere. However, these differences in efficiency do not translate to differences in the instantaneous precipitation rate across the synoptic regimes because of a compensating change in the net condensation rate. This is driven by variations in cloud updraft velocity, which is larger in drier environments than in moist environments. Key Points: First long‐term observational estimate of precipitation efficiency at convective scales for a location in the tropics is presented Precipitation efficiency increases with environmental humidity and decreases weakly with instability (CAPE) Compensation between precipitation efficiency and updraft velocity results in weak dependence of precipitation intensity on synoptic regime